Occurrence of Giardia in the effluents of a waste water treatment plant in Dhaka (Bangladesh Journal of Zoology, 2012)
The present study was designed for the qualitative and quantitative detection of Giardia in the Pagla Sewage Treatment Plant (PSTP) in Dhaka. The physico-chemical parameters of the sewage water were also recorded. Total 72 raw and treated samples were collected from PSTP throughout the year 2008 and these were processed with the Formol-Ether Concentration method and IMS followed by microscopy to identify Giardia in the sewage water. The protozoan parasite Giardia was abundant (2.23±1.44 × 105 cyst/l) in the sewage water dominating the sampling sites-Grit chamber (44%), Measuring chamber (34%) and Outlet lagoon (38%). A low abundance of Giardia in the PSTP starting from the first point to the last one indicates the waste water treatment efficiency for removal of the pathogen. A significant correlation was found for log (number of Giardia +1) with turbidity (r= 0.729) and TDS (r= 0.536) at 0.01level.DOI: http://dx.doi.org/10.3329/bjz.v39i2.10578 Bangladesh J. Zool. 39(2): 147-156, 2011